2018
DOI: 10.1016/j.transci.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

0.9% NaCl (Normal Saline) – Perhaps not so normal after all?

Abstract: Crystalloid infusion is widely employed in patient care for volume replacement and resuscitation. In the United States the crystalloid of choice is often normal saline. Surgeons and anesthesiologists have long preferred buffered solutions such as Ringer's Lactate and Plasma-Lyte A. Normal saline is the solution most widely employed in medical and pediatric care, as well as in hematology and transfusion medicine. However, there is growing concern that normal saline is more toxic than balanced, buffered crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 46 publications
(51 reference statements)
2
45
1
3
Order By: Relevance
“…This article is protected by copyright. All rights reserved for clinical use as previously reported by our group (Blumberg N et al, 2018). The collected washed solution can then later sterilized in special blood packages obtainable from a biotech company, which can be used in some well-established means for their sterilization and pathogen reduction by the UVC.…”
Section: Accepted Articlementioning
confidence: 98%
“…This article is protected by copyright. All rights reserved for clinical use as previously reported by our group (Blumberg N et al, 2018). The collected washed solution can then later sterilized in special blood packages obtainable from a biotech company, which can be used in some well-established means for their sterilization and pathogen reduction by the UVC.…”
Section: Accepted Articlementioning
confidence: 98%
“…1 However, the acidic nature of "normal" saline had not been appreciated and the potentially beneficial effect of permissive hypotension was not widely practiced. [2][3][4] More recently, an increasing body of evidence has demonstrated that aggressive resuscitation with crystalloid fluids might actually be detrimental to trauma patients, [5][6][7][8][9][10][11][12] and so modern trauma resuscitation protocols minimize their use.…”
Section: Conclusion: This Model Predicted Improvedmentioning
confidence: 99%
“…In silico model of the dilutional effects of conventional component therapy versus whole blood in the management of massively bleeding adult trauma patients Jansen N. Seheult ,1,2 Michelle N. Stram, 1 Jason Sperry, 3,4 Philip C. Spinella, 5 Darrell J. Triulzi, 1,2 and Mark H. Yazer 1,2 BACKGROUND: There are multiple approaches to the blood product and fluid resuscitation of a bleeding trauma patient. An in silico model of different trauma resuscitation strategies was constructed to predict their effects on the volumes of the different body fluid compartments and on several important hemostatic factors.…”
mentioning
confidence: 99%
“…Its virtues include long clinical experience and low cost compared with buffered crystalloid solutions or albumin. However, there are now serious concerns about the safety of normal saline . It contains strikingly higher quantities of chloride and is relatively acidic, which predisposes to hyperchloremic metabolic acidosis in some patients .…”
Section: Introductionmentioning
confidence: 99%
“…It contains strikingly higher quantities of chloride and is relatively acidic, which predisposes to hyperchloremic metabolic acidosis in some patients . It is unbuffered and hypertonic compared with the electrolyte composition of plasma and other solutions .…”
Section: Introductionmentioning
confidence: 99%